The Gut Microbiota Links Dietary Polyphenols With Management of Psychiatric Mood Disorders - Westfall, Susan; Pasinetti, Giulio Maria (Frontiers in Neuroscience, 2019)
The pathophysiology of depression is multifactorial yet generally aggravated by stress and its associated physiological consequences. To effectively treat these diverse risk factors, a broad acting strategy is required and is has been suggested that gut-brain-axis signaling may play a pinnacle role in promoting resilience to several of these stress-induced changes including pathogenic load, inflammation, HPA-axis activation, oxidative stress and neurotransmitter imbalances. The gut microbiota also manages the bioaccessibility of phenolic metabolites from dietary polyphenols whose multiple beneficial properties have known therapeutic efficacy against depression. Although several potential therapeutic mechanisms of dietary polyphenols towards establishing cognitive resilience to neuropsychiatric disorders have been established, only a handful of studies have systematically identified how the interaction of the gut microbiota with dietary polyphenols can synergistically alleviate the biological signatures of depression. The current review investigates several of these potential mechanisms and how synbiotics, that combine probiotics with dietary polyphenols, may provide a novel therapeutic strategy for depression. In particular, synbiotics have the potential to alleviate neuroinflammation by modulating microglial and inflammasome activation, reduce oxidative stress and balance serotonin metabolism therefore simultaneously targeting several of the major pathological risk factors of depression. Overall, synbiotics may act as a novel therapeutic paradigm for neuropsychiatric disorders and further understanding the fundamental mechanisms of gut-brain-axis signaling will allow full utilization of the gut microbiota’s as a therapeutic tool.